OPTIMALISASI BAHAN AJAR, MEDIA, DAN SUMBER BELAJAR DALAM PEMBELAJARAN PAI - Susi Annisa Putri; Dimas Aldi Pratama; Samsul Susilawati (PT. Hasba Edukasi Mandiri, 2025)
This article examines the strategic roles of teaching materials, media, and learning resources in Islamic Religious Education (PAI) instruction in schools and madrasahs. These three components are regarded as essential elements that complement each other to create an effective, efficient, and enjoyable learning environment. Teaching materials serve as the primary reference containing curriculum-based content, thus significantly influencing students’ understanding and learning outcomes. Instructional media, whether in the form of tools or technology, play a role in delivering information in an engaging and varied manner, thereby increasing students’ motivation and involvement in the learning process. Learning resources provide broader references, enabling students to explore knowledge beyond the main teaching materials. With optimal utilization, these three elements can enhance the quality of PAI learning, support the achievement of educational goals, and contribute to the development of students’ character and moral values. This article also discusses the definitions, types, and benefits of each component, and emphasizes the importance of teachers’ understanding of the roles of teaching materials, media, and learning resources in supporting a holistic learning process in schools and madrasahs.